Spatiotemporal Variations of the Rainfall Erosion in West Azerbaijan Province - Habib Nazarnejad; Tara Shahhossein; Farrokh Asadzadeh (جغرافیا و پایداری محیط, 2018)
Rainfall erosion is a key factor in soil erosion processes. Determining the quantitative values of the rainfall erosion factor is assumed as a first step in sustainable management of soil and water resources. In terms of quantity, rainfall erosion is one of the characteristics that has the highest correlation with soil losses. Modified Fournier index (MF) is a simple rainfall erosion index which is widely used as a quantitative index in soil erosion projects. In this research, the spatiotemporal variation of the modified Fournier index was determined in west Azerbaijan province for a twenty-year period from 1993 to 2012. A total of 66 rain gauge data were used to determine the MF and precipitation concentration index (PCI). The spatial pattern of the MF and PCI were mapped by Kriging. The findings indicated that there was a wide range for MF, 28.28-116.22 mm, and the highest value of MF was observed in southwest of the region while the smallest values of the MF is located at the northeast of the region. Descriptive statistics of the PCI indicated that the 80 percent of the stations shows a seasonal pattern of rainfall distribution, while 20 percent of the stations have a moderate seasonal rainfall distribution pattern. There was a strong positive relationship between the annual rainfall and MF (r= 0.934, p< 0.001). A significant relationship was not observed between the PCI with annual rainfall and MF. The spatial patterns of the MF and annual rainfall showed a regular decreasing from south to the north of the region. Extended Abstract 1-Introduction Climate change in the current era is one of the most important environmental challenges. Precipitation is one of the most important climate elements directly affecting the availability of water resources. Low amount of precipitation and its extreme fluctuations in the daily, seasonal and annual scales is an inherent characteristic of Iran’s climate. Due to significant impacts of rainfall on water resources such as groundwater, surface water, and snow reservoir, some indices, Standard Precipitation Index (SPI) and Precipitation Concentration Index (PCI), are applied to explain its changes. SPI index includes applicable indices that are used in most studies, while PCI index has been introduced in recent years. Different indices have been used to assess the density of precipitation, inwhich the Precipitation Concentration Index (PCI) is recommended, for it provides information on long-term total variability in the amount of received rainfall. Rain erosion is recognized as a key factor on erosion. Accurate knowledge of the amount of rainfall erosion in a region is considered as a primary step in the sustainable management of soil and water. Early indices (Fournier and modified Fournier) are one of the most important indicators of rainfall erosion, which have widely been used in soil erosion studies due to easy calculation compared with other indices. 2-Materials and Methods West Azerbaijan province with an area of 37210 square kilometers (including the Urmia Lake) is the thirstiness province of Iran in extent which is located at a geographic location of 44° 3' to 47° 23' East longitude and 35° 58' to 39° 3344' Northern latitude. In this study, rainfall data from gauge stations of West Azerbaijan (Iran) were used in order to investigate of Precipitation Concentration Index. Referring to Iran water resources management, information, including daily rainfall data, geographical coordinates of the stations and years of statistics, received. After reviewing, the stations with incomplete data were excluded and finally, 66 rain gauge stations were selected. Information on daily rainfall for a period of 20 years (1993-2012) was reviewed in terms of homogeneity and normality using Kolmogorov-Smirnov test and was used for calculating of PCI index. The aim of this research is to establish a regression relationship between the early indices with the EI30 index for studying the spatial and temporal changes in the rainfall erosion index during the period of 1993-2012 in West Azerbaijan province. Therefore, the data of 66 rain gauges and 13 rain-fed stations were used and erosion indices and precipitation concentration index of the region were calculated and spatial changes map was mapped using the Kriging method. 3-Results and Discussion Average rainfall in the entire area during a twenty-year period is approximately 325 mm. The mean value of PCI was 16.66 indicating the seasonal distribution of rainfall in the province. The minimum value of PCI for the area was 12.36 demonstrating the fair distribution of rainfall and the maximum value of this index for the entire period as 22.17 that represents the distribution of rainfall is very seasonal. The important note is the few differences in statistics related to Precipitation Concentration Index so that during the period of two decades, mean changes of PCI is less than 2%. The EI30 index has the highest correlation with the overall corrected Fournier index (R2 = 0.9). The EI30 index variation is very high in the province and is located in a range of 62.54 to 230.05 mega Jules millimeter per hectare per hour per year. The maximum erosion was observed in the southwestern part of the province and in the forests of Piranshahr and Sardasht, and at least in the northern and eastern of the province. According to the precipitation concentration index, rainfall pattern in the province was observed as relatively seasonal and seasonal. In terms of statistical period, rainfall amount and erosion indices showed an increase during the second decade compared to the first decade. The results showed that the erosive indices and the amount of annual precipitation decrease regularly by moving to higher geographic latitudes. 4-Conclusion In general, in lower latitudes, rainfall is higher in parts of the western highlands and in the southwest of the province which is decreasing regularly by moving towards the northern and eastern regions. This is in line with the results of Jalali and Shafi'i (2012) investigations conducted for West Azarbaijan province. ). Examining the annual and seasonal changes of rainfall in different climate zones by Azarakhshi et al (2013), and Ghaderpour (2014) by the assessment of precipitation spatial trend in the watershed of Lake Urmia announced that the province has a rising and declining trend in rainfall on an annual basis and the results are in accordance with this study.